PENGARUH KINERJA KEUANGAN TERHADAP KONTINUITAS USAHA PADA PT. FEDERAL INTERNATIONAL FINANCE CABANG MAKASSAR - Salmiaty Taty (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2013)
This study aimed to analyze the effect of Financial Performance In Business continuity PT.Federal Makassar International Finance Branch to the method used is descriptive comparative method is a method in which datadikumpulkan , compiled , interpreted , and analyzed to give full details of the problem dihadapi.Metode Independent Variable Ratio analysis is to compare the existing theories with practices found in the company and attract kesimpulan.Hasil research shows that : a significant influence and positive impact on increasing federal income Makassar International Finance Branch and significant influence and negative influence of the increase in Federal income period years 2008-2012. Then that the higher the financial ratios we can conclude finance operational activities are not efficient . When all the activities are carried out efficiently finance runs , then the profits will also be greater , which in turn will improve the financial performance of the finance.